An Upland community in transition institutional innovations for sustainable development in rural Philippines - Rola, Agnes C. (SEAMEO SEARCA, 2011)
All over Southeast Asia, rural communities are in transition to a sustainable status. This book explores how an environmentally fragile upland community in rural Philippines coped with and responded to economic and environmental tensions brought about by a globalized economy and decentralization. This in turn gave rise to local power especially in the management of natural resources.